Solvent Extraction of Palladium(II) from Hydrochloric Acid Solution Using Octyl Benzothiazolyl Sulfide - Chang, Jun; Huang, Zhangjie; Xi, Mangsong (Asian Journal of Chemistry, 2011)
A new octyl benzothiazolyl sulfide (OBTS) was synthesized and used in the extraction of Pd(II) from hydrochloric acid solution. Pd(II) was extracted quantitatively with octyl benzothiazolyl sulfide in toluene. Thiourea solution could be used as stripping agent. Extraction parameters of Pd(II), including octyl benzothiazolyl sulfide concentration, palladium concentrations in the feed solution, contact time of aqueous and organic phases, organic/aqueous (O/A) phase ratio, thiourea concentration and H+ concentration of aqueous phase, were studied in detail. IR analysis of Pd(II)-OBTS complex indicated that octyl benzothiazolyl sulfide coordinated with palladium via the thiazole N atom.